Prevalence of goiter according to etiology among adolescents seen at the Philippine General Hospital out-patient clinic - Abad, Lorna R. (Theses--(MS in Epidemiology-Clinical Epidemiology) University of the Philippines Manila)
Objectives: 1) To determine the causes of goiter and their prevalence among adolescents seen at the Philippine General Hospital Out-patient Department (PGH-OPD) 2) To determine the pattern of distribution of the different causes according to geographic origin or place of residence 3) To determine the association of age, weight, height, body surface area, duration of illness and etiology with thyroid volume. Methods: This is a cross-sectional study. All adolescents age 10-18 years with complaints of neck mass or referred for neck mass on physical examination who had diffuse thyromegaly on palpation and were clinically and biochemically euthyroid from October 1999 to february 2001 were considered as cases of goiter in the study. A thorough medical history was taken and complete physical examination was done. Thyroid grading was based on the 1960 WHO clinical criteria and actual size was determined by ultrasonography. Thyroid function tests (T3, T4, TSH) thryoid antibodies (TPO, TGA) and urine iodine excretion were determined. All adolescents in the same group who consulted at the PGH-OPD during the study period was used as the denominator for the prevalence estimates. Results: Out of a total 2720 adolescents consulting at the PGH-OPD, 179 cases of diffuse, euthyroid goiter were detected. There were 172 females and 7 males. The overall prevalence of diffuse goiter based on the 1960 WHO Clinical Classification was 6.68% (95% CI: 3.02-1034). Thyromegaly was caused by iodine deficiency (n=43; 24.0%), lymphocytic thyroiditis (n=31;17.3%) and simple colloid goiter (n=105,58.5%). Prevalence rates of the different causes were: 1.8% (95% CI: 0.15-3.75) for Iodine Deficiency; 1.14% (95% CI: 0.42-2.70) for Lymphocytic Thyroiditis; and 3.64% (95%CI: 2.06-4.78) for Simple Colloid Goiter. Using the 9160 WHO Classification, only 4 had severely enlarged gland. No significant association was found between thryoid volume and age, weight, height, body surface area and duration of illness. However, age, body surface area and etiology had the highest correlation coefficients with thyroid volume. More than 50% of children with goiter on clinical ssessment had normal thyroid volume on ultrasound based on the WHO thryoid volume reference standard.
Keywords: Goiter; Thyroid gland--diseases.